In situ molecular weaving of ionic polymers into metal-organic frameworks for radioactive anion capture - Xinghao Li; Xiang Lin; Zhenzhen Feng; Feng Chen; Qihang Huang; Linlin Zheng; Hongwei Wu; Jiayin Yuan; Yaozu Liao; Weiyi Zhang (Nature Communications)
Abstract Encapsulation of polymer chains into nanochannels of metal-organic frameworks (MOFs) to construct polymer-MOF hybrid materials can retain the desired properties of two disparate materials. However, the facile fabrication of such hybrids remains challenging, given the difficulty in unraveling entanglement of polymer chains and constraining them into ordered conformations. Herein, we introduce an in situ molecular weaving strategy to construct ionic polymer-MOF hybrid materials, employing shear forces and coordination interactions to untangle cationic polymer chains and guide their realignment within MOF nanochannels during framework formation. Notably, this realignment promotes uniform polymer distribution and exposes more anion-exchange sites. The resulting hybrids capture ReO4 ¯ (a nonradioactive surrogate of 99TcO4 ¯) with a capacity of 438 mg g-1 and reach adsorption equilibrium within 20 min. Characterization and theoretical calculations reveal that the hydrophobic pores in the hybrid materials confer strong affinity toward less hydrated 99TcO4 ¯ anions, thereby enhancing their selectivity over competing anions.